Factors Affecting Physical Fitness in STIKES Harapan Ibu Jambi Employees in 2021 - Winda Senthya Mitrinas; Renny Listiawaty; Suroso Suroso (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Physical fitness is a person's ability to carry out daily tasks easily, without feeling excessively tired, and still having energy left or reserves to enjoy his spare time and for urgent needs.This research is a quantitative descriptive study with a cross sectional approach. The purpose of this study was to determine the description and factors that influence the physical fitness of STIKES Harapan Ibu Jambi employees. The population in this study were all employees of STIKES Harapan Ibu Jambi, sampling was carried out using purposive sampling with a research sample of 34 employees. The results showed that of the 34 employees of STIKES Harapan Ibu Jambi, 28 employees (82.4%) were in the less fit category and 6 employees (17.6%) were in the fit category. This study shows that there is a significant relationship between physical activity and physical fitness with a p-value of 0.02, and nutritional status with a p-value of 0.01, while smoking habits have a p-value of 1.00 which shows no significant relationship. with the physical fitness of the employees of STIKES Harapan Ibu Jambi. Low employee fitness, can be improved by improving exercise habits by increasing the intensity and time of exercise. Physical exercise is the same as physical exercise that is carried out in a planned and repeated manner to improve or maintain physical health.